La reconnaissance législative accordée aux Acadiens du Nouveau-Brunswick avant la Confédération (1784 à 1867) - Migneault, Gaétan (Acadiensis, 2012)
Sociologists attribute the Acadian collective awakening to the period 1860-1880. Yet, despite the marginalization of Acadians and their lack of organization, the law appears to have recognized them as a community many years before the 1860s. In particular, provincial legislation allowed their exclusion from a uniform “poor rate” regime to let them care for their poor, a publicly financed lazaretto was dedicated to their medical treatment, and the legislature provided to some Acadians in southeastern New Brunswick their own fiscal regime to assist the poor. This article explores the recognition of Acadians’ communal aspirations by the law.